2017
DOI: 10.1371/journal.pone.0180314
|View full text |Cite
|
Sign up to set email alerts
|

Generation of monoclonal pan-hemagglutinin antibodies for the quantification of multiple strains of influenza

Abstract: Vaccination is the most effective course of action to prevent influenza. About 150 million doses of influenza vaccines were distributed for the 2015–2016 season in the USA alone according to the Centers for Disease Control and Prevention. Vaccine dosage is calculated based on the concentration of hemagglutinin (HA), the main surface glycoprotein expressed by influenza which varies from strain to strain. Therefore yearly-updated strain-specific antibodies and calibrating antigens are required. Preparing these q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Spleen cells were electrofused to the NS0 myeloma cell line using as described previously. 36,37 Hybridoma supernatants were screened for appropriate antigen specificity by ELISA on EGFRvIII and EGFR recombinant proteins. Briefly, half-area 96-well plates (Costar #3690) were coated with 25 mL per well of immunogen at 5 mg/mL in PBS and incubated overnight at 4 C. Microplates were washed three times in PBS and blocked for 30 min with PBS containing 1% bovine serum albumin (BSA; Sigma, catalog #A7030).…”
Section: Anti-egfrviii Mab Generation and Screeningmentioning
confidence: 99%
“…Spleen cells were electrofused to the NS0 myeloma cell line using as described previously. 36,37 Hybridoma supernatants were screened for appropriate antigen specificity by ELISA on EGFRvIII and EGFR recombinant proteins. Briefly, half-area 96-well plates (Costar #3690) were coated with 25 mL per well of immunogen at 5 mg/mL in PBS and incubated overnight at 4 C. Microplates were washed three times in PBS and blocked for 30 min with PBS containing 1% bovine serum albumin (BSA; Sigma, catalog #A7030).…”
Section: Anti-egfrviii Mab Generation and Screeningmentioning
confidence: 99%
“…This study further investigated observations from previous work using glycosylated peptide- protein conjugates to raise monoclonal antibodies for quantification of multiple strains of influenza 33 . During these studies, conserved HA peptide epitopes were lactosylated to increase peptide solubility but it was also observed to influence the epitope specificity of the raised antisera.…”
Section: Discussionmentioning
confidence: 89%
“…Previously, we have demonstrated that the KLH conjugate of a glycosylated HA peptide (a.a. 1–14 HA2) resulted in improved immunogenicity and specificity towards the peptide core sequence 33 . We reasoned these improvements arose from the effect of peptide glycosylation by (1) improvement on peptide solubility, and (2) masking the terminal neo-epitope present on the KLH conjugates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR expressing Jurkat cells or primary T cells were generated as indicated elsewhere and assessed for surface expression using an Alexa-Fluor647 labelled murine monoclonal anti-sdAb antibody generated in house. In brief, mice were immunized with sdAb fragments produced in e coli followed by B cell isolation and hybridoma formation as previously reported[32]. Clonal hybridoma supernatants were screened for reactivity against a number of plate bound sdAbs to identify broadly sdAb-reactive monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%